Analisis Standar Kualifikasi Akademik Guru SD di Kecamatan Kras Kabupaten Kediri - Harun Al Rasyid (Widyagogik)
The study with title of “Analisis Standar Kualifikasi Akademik Guru SD di Kecamatan Kras Kabupaten Kediri” have to know abstract leval of academic qualified teacher of elementary school  in subdistrict of Kras in Kediri District. Research data is quantitative data was analysed by descriptive, because in this study to analyse of academic qualified standard teacher of elementary school  in subdistrict of Kras in Kediri District. The result of this study showed that counted 174 teacher of elementary school  (77%) in subdistrict of Kras in Kediri District which have achieved academic qualified from total 226 teacher of elementary school. This means that counted 52 teacher of elementary school (23%) academic qualified including which qualify. Amount 23%  the predominated by teacher bachelor (DII) is counted 17 teacher (7,5%). This amount including low if as compared to academic qualified which nationally qualify.